Does Administrative Data Reflect Individual Experience? Comparing an Index of Poverty with Individually Collected Data on Financial Well-being in a Multi-Ethnic Community. Issue 4 (4th November 2015) - Prady, Stephanie L.; Bloor, Karen; Bradshaw, Jonathan; Tunstall, Helena; Petherick, Emily S.; Pickett, Kate E.
Abstract : The Income Deprivation Affecting Children Index (IDACI) uses administrative data to count children living in households in receipt of both in-work and out-of-work means-tested benefits and provides small area ranking as an indicator of child poverty in neighbourhoods. Benefit take-up rates within an area will affect its reliability. We aimed to examine benefit take-up rates and compare area ranking by the IDACI with ranking using individually reported data across areas of varying ethnic composition. Mothers living in areas with high minority ethnic density were less likely to report claiming a benefit than those in majority White or mixed areas, despite reporting lower incomes. The correlation between self-reported material difficulties and worsening IDACI rank was much lower in areas characterised by minority ethnic populations. Further investigation into the performance of area-based deprivation measures in areas with high minority ethnic density is needed.